Macho, Thomas (2021). Arrebatar la vida: El suicidio en la Modernidad - G. J. Peña, Alejandro (Enrahonar. An international journal of theoretical and practical reason, 2023)
Macho, Thomas (2021) Arrebatar la vida: El suicidio en la Modernidad Alberto Ciria (trad.) Barcelona: Herder, 521 p. ISBN 978-84-254-4290-2